Clinico-epidemiological profile of dengue fever cases admitte at tertiary care hospital, Rajkot, Gujarat, India - Oza, Jasmin R.; Patel, Umed V.; Gajera, Kshama D. (International Journal Of Community Medicine And Public Health, 2016)
Background: Dengue fever (DF) and its severe forms - Dengue haemorrhagic fever (DHF) and Dengue shock syndrome (DSS) have emerged as a notable public health problem in recent decades in terms of the mortality and morbidity associated with it. Methods: A cross-sectional prospective study was conducted at PDU Government Medical College, Rajkot during 1st January to 31st December, 2014. All confirmed Dengue cases were admitted in this institute during 2014 included in the study. The data entry was done in Microsoft Office Excel 2007 and analysis was done using the same software and appropriate tests were applied. Results: This study included 145 patients who were admitted to the institute during the calendar year 2014. 62% were males. 69% were in the age group 15-44 yrs. 59% cases were from rural origin. During September to December, 2014, 80% cases were admitted. 74% cases were consulted by doctor before admission at PDU Government Medical College, Rajkot. Fever was present in all the cases i.e. (100%), followed by myalgia (99%), headache (96%), vomiting (78%) and epistaxis (63%). Majority of the cases presented with Classical Dengue fever i.e. (90%) followed by DHF (10%). Most common complication was bleeding from nose and mouth i.e. (66%). No any death due to Dengue was reported during study period. 93% cases were discharged and 7 % cases were DAMA from PDU Government Medical College, Rajkot. Conclusions: The most common age group for Dengue fever was 15-44 yrs. Most of the patients were male and also from rural origin. Most of the cases occurred during the period of September to December, 2014. Fever was present in all the cases and bleeding from nose and mouth was the commonest complication of Dengue. No any death due to Dengue was reported during study period.